Correlates of Stillbirths at Nyeri Provincial General Hospital, Kenya, 2009-2013: A Retrospective Study - Joyce J. Cheptum, Msc; Nelly Muiruri, MA; Ernest Mutua, MPH; Moses Gitonga, MPH; Mwangi Juma, MBBS (Global Health and Education Projects, Inc., 2016)
Background: Death of a baby in-utero is a very devastating event to the mother and the family. Most stillbirths occur during labor and birth with other deaths occurring during the antenatal period. Millions of families experience stillbirths, yet these deaths remain uncounted, and policies have not been clearly stipulated to address this issue. The aim of the study was to identify the possible causes of stillbirths as recorded in the medical records. Methods: A retrospective study looking at medical records of women who experienced stillbirths between 1st January 2009 and 31st December 2013 at Nyeri Provincial General Hospital, Kenya. The hospital records containing cases of stillbirths were retrieved and data abstraction forms were used to collect data and information. Results: Both fresh and macerated stillbirths were equally common. The stillbirth rate was 12.2 per 1,000 births. There was signifi cant association between stillbirths and the clients who were referred and reason for referral, (p=0.029) and (p=0.005), respectively. The number of ANC visits during pregnancy was also signifi cant (p=0.05). Mode of delivery and the reason for cesarean section were signifi cantly associated with stillbirths, (p=0.003) and (p=0.032), respectively. The type of labor and delivery complications experienced was associated with stillbirths (p= 0.022). Conclusion and Global Health Implications: There were several factors associated with stillbirths thus efforts should be made to establish approaches aimed at prevention. Addressing the causes of stillbirths will contribute to reduction of perinatal mortality. Key words: Stillbirths • Medical Records • Labor • Delivery • Referral • Nyeri • Kenya Copyright © 2016 Cheptum et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.